THE CURRENT STATE OF ROADSIDE LANDSCAPES IN BUKHARA REGION AND THEIR UTILIZATION - Halimova, Gulshan Subhonovna; Kalandarova, Dilobar Davronovna; Nuriddinov, Rajabmirzo Maxsudovich; Odilova, Khurshida Ortiqovna (SCIENCE and SOCIETY, 2026)
This article analyzes the current state of road and roadside landscapes in the Bukhara region and their utilization. The study examines the formation of roadside landscapes using the examples of the international highways A379, A380, and M37, highlighting their natural-geographical characteristics as well as their ecological significance. Furthermore, the research identifies insufficient development of roadside infrastructure in these areas, shortcomings in service systems, and existing environmental problems. The article also provides scientifically grounded recommendations for the effective organization of roadside landscapes, greening, and increasing biodiversity. The results of the study are of significant importance for regional development, transport geography, and ensuring environmental sustainability.